POLÍTICA, PENSAMENTO E POESIA: AS MOIRAS TECEDEIRAS NOS DESTINOS POÉTICOS DE FERREIRA GULLAR - Boniatti, André (2023)
This thesis analyzes the poetical work of Ferreira Gullar, seeking its aesthetic, political theoretical and philosophical influences in what concerns phenomenology. The journey of Gullar, born in 1930 and died in 2016, in terms of his intellectual production, begins mainly after 1950, with his first book A Luta Corporal. In our thesis, we point out three phases to his works, not only temporally distincted, but through subtle, although vehement, changes in style and thought. And, for that, we classified the phases in a poetic way using the Greek mythical figures of the three moirai: Clotho, fate that represents the birth; Lachesis, who represents the paths traced in life; and Atropos, representative of death. The use of these figures treats in a playful way the paths of Gullar's poetry, which also seems to run through the scope of a personal genesis, then the concern with the experience of men in society and, finally, the phenomenological and existentialist philosophical conscience, deepening themes like death and metapoetry. Keeping, by methodology, the teachings of the Comparative Literature discipline, in the first chapter we introduce the way we use it to carry out our thesis. Because, in the second chapter, we evaluate the influences of the poet, so we could affirm him as a primordial poetic voice of contemporaneity, following Carlos Drummond de Andrade and João Cabral de Melo Neto, mainly. To do so, we used a vast theoretical framework, based on names such as Lima (1968), Senna (1980), Teles (1979), Linhares (1976), among others. In the third chapter, we recognized the way in which Gullar understood Brazilian social life, understanding his communist thought, under the works of Lukács (2016), Lafetá (2000), Eagleton (1976) and others. And then, in our fourth chapter, based on names such as Heidegger (2016), Sartre (2015), Gumbrecht (2010) and Adorno (2021), we understood his phenomenological and existentialist thinking. We conclude, finally, that Ferreira Gullar stands as the most eminent voice of his generation, regarding the development of his poems and his popularity, being one of the main voices of our literary history, when passing through and describing, in poetry, the history of our contemporary Brazil.